2020
DOI: 10.1016/j.numecd.2020.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Quarantine during COVID-19 outbreak: Changes in diet and physical activity increase the risk of cardiovascular disease

Abstract: Aims: CoV-19/SARS-CoV-2 is a highly pathogenic virus that is causing a global pandemic with a high number of deaths and infected people. To contain the diffusion of infection, several governments have enforced restrictions on outdoor activities or even collective quarantine on the population. The present commentary briefly analyzes the effects of quarantine on lifestyle, including nutrition and physical activity and the impact of new technologies in dealing with this situation. Data synthesis: Quarantine is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
441
3
40

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(495 citation statements)
references
References 78 publications
(86 reference statements)
11
441
3
40
Order By: Relevance
“…In fact, in this study more half of the participants reported anger and heightened levels of stress during the lockdown. For many people, the response to stress, distress, and emotional disturbance is not to avoid food but possibly to increase the consumption of energy-dense foods (18). It has been proposed that this emotionally-induced eating comes as a result of interference of eating by emotions, a by-product of emotions, and a consequence of regulatory processes (i.e., emotions may regulate eating, and eating may regulate emotions) (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in this study more half of the participants reported anger and heightened levels of stress during the lockdown. For many people, the response to stress, distress, and emotional disturbance is not to avoid food but possibly to increase the consumption of energy-dense foods (18). It has been proposed that this emotionally-induced eating comes as a result of interference of eating by emotions, a by-product of emotions, and a consequence of regulatory processes (i.e., emotions may regulate eating, and eating may regulate emotions) (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gender and living conditions, weight status was shown to affect the odds of adopting unhealthy behaviors, whereby in this study, having a BMI ≥ 25 kg/m 2 were more likely to report higher dietary intake, increase in weight, lower physical activity and increased smoking. It has been suggested that during quarantine, patients suffering from obesity may experience higher levels of stress which in turn makes them more vulnerable to over-eating and sedentary lifestyle, thus predisposing them to further weight gain (18). These ndings suggest that obese subjects must be carefully informed about the risk of an unhealthy lifestyle during the quarantine due to the increasing risk of disease associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, following the main focus of this paper, such sudden lifestyle changes might have both positive and negative impacts on food consumption. Existing studies are controversial in this sense, since some studies-such as [4]-have found evidence of healthier lifestyles during the lockdown, while others have revealed problems emerging from unsafe lifestyles during quarantine [6]. The pandemic has also abruptly changed food consumption habits in the short term, and it remains to be seen whether these changes will persist over time.…”
Section: How Covid-19 Has Affected Our Lifestyles: the Main Picturementioning
confidence: 99%
“…In the aim of dealing with the COVID-19 pandemic, the majority of countries have at some point implemented the total or partial quarantine of the population. Many mental health specialists have alerted already that the “lock down” phenomenon led to the raise of the number of patients with anxiety and higher stress levels, but also caused the changes in the lifestyle especially concerning the eating habits and lower physical activity ( Mattioli et al, 2020 ). The chronic stress, perhaps arising as a consequence of the quarantine and social isolation or on the other hand, fear of political and financial aftermath, could lead to increase of the activity of the sympathetic nervous system which may cause increased risk of mortality in patients with pre-existing CVD ( Steptoe and Kivimäki, 2012 ; Mattioli et al, 2020 ).…”
Section: Covid-19 Pandemic Societal Effect As a Cardiovascular Risk Fmentioning
confidence: 99%
“…Many mental health specialists have alerted already that the “lock down” phenomenon led to the raise of the number of patients with anxiety and higher stress levels, but also caused the changes in the lifestyle especially concerning the eating habits and lower physical activity ( Mattioli et al, 2020 ). The chronic stress, perhaps arising as a consequence of the quarantine and social isolation or on the other hand, fear of political and financial aftermath, could lead to increase of the activity of the sympathetic nervous system which may cause increased risk of mortality in patients with pre-existing CVD ( Steptoe and Kivimäki, 2012 ; Mattioli et al, 2020 ). In a study that was following a cohort of 1267 patients older than 65 years in a period of 10 years, it was shown that the social isolation was highly connected with the increased risk of mortality in these patients ( Yu et al, 2020 ).…”
Section: Covid-19 Pandemic Societal Effect As a Cardiovascular Risk Fmentioning
confidence: 99%